Atmospheric ice monitoring system operation at Remote locations in cold region - Virk, Muhammad Shakeel; Rashid, Taimur; Mustafa, Mohamad Y (International Journal of Energy and Environment, 2013)
Open Access, Creative Commons Attribution Licence required. Link to publisher's version: https://www.ijee.ieefoundation.org/vol4/issue5/IJEE_14_v4n5.pdf The problems encountered in installation, maintenance and operations of equipment in the cold climate regions are far more complicated than others. The contributing factors and problems that can affect the system operation and performance should be identified, assessed and focused within well-defined parameters before its installation in cold climate regions. The harsh cold environment, could not only directly impact the system performance, but can also indirectly contributes to the associated factors, which could result in the delayed maintenance and system monitoring activities. This paper describes the issues related to meteorological ice monitoring system’s operation in cold environment and also practical problems are identified and assessed, based on their impact on the overall system performance. The attributing factors causing such problems are overviewed and relationship between key parameters and system performance is discussed.